Sheer madness : sex, lies and politics : a memoir - Murray, Jan N. ([Chatswood, NSW] : MIRA, 2014)
Sheer Madness: Sex, Lies and Politics explodes off the page with honesty and humour. Jan Murray - known to millions of Australians as the Cabinet Minister's wife who rocked the nation with her cheeky 60 Minutes revelation of having sex on his desk - now goes hell-for-leather to tell her story. A deaf-eared kid from a working-class family who left school at fourteen, Jan married her teenage heart-throb and had five children by the age of twenty eight. She discovered feminism in her thirties, studied for a university degree, became a Canberra political insider, ran a successful PR company, and mixed it with princes, presidents and pop stars before, devastatingly, hitting the wall. Hers is a story that packs a mighty punch; sometimes biting and often enlightening but always entertaining!.
Imprint: Mira.
Online resource; title from title details screen (OverDrive, viewed August 31, 2015)
Keywords: Murray, Jan; Women -- Australia -- Biography; Femmes -- Australie -- Biographies; Family & Relationships - General; Women; Australia; Australian; Autobiography; Electronic books; Biographies